Determining National E-Readiness Dimensions based on System Approach - Elham Ziaeipour; Ayoub Mohammadian; Farid Khoshalhan; Alireza Taghizade (Journal of Information Technology Management)
In this paper, with studying existing e-Readiness evaluation models and their well-known drawbacks and advantages, we propose a new comprehensive classification for e-Readiness evaluation parameters. With this aim in mind; at the beginning we identify and study all popular e-Readiness evaluation parameters in international, national, industrial, organizational and individual levels, then we categorize identified parameters based on value oriented system approach and content analysis method. After that we extract importance and priority of each parameter by using Shannon’s entropy, additionally, based on field study and using statistical methods such as binominal and Friedman test, the priority of each dimention is identified.